The Perception of elementary school students’ parents toward the profile of an artist and an art educator: Persepsi orang tua siswa sekolah dasar terhadap profil seniman dan pendidik seni - Zufar, Anaan; Maulida, Andini Rastya; Supendi, Nadia Aulia Fitarbiyati Filmuslim; Iklima, Putri Dera (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2025)
Parents' views on guiding their children's career choices are very influential. Although art is becoming more widely recognised, there is still a perception that art is merely a hobby, not a viable career. This study examines parents' perceptions of the professions of artists and art educators using a phenomenological approach and in-depth interviews in a village in Java. The results reveal varied perspectives; some parents appreciate art for its role in character and cultural development, while others question the economic prospects in this field. Artists are seen as creative but less valued compared to more established professions. Art teachers are often viewed as supplementary educators of lesser importance. These findings underscore the importance of education, family, and community in fostering support for the arts as a valuable and equal career option.   _______________________________________________________________________________   Pandangan orang tua dalam mengarahkan pilihan karier anak sangat berpengaruh. Meskipun seni semakin dikenal, masih ada anggapan bahwa seni hanya sekadar hobi, bukan karier yang layak. Penelitian ini mengkaji persepsi orang tua terhadap profesi seniman dan pendidik seni dengan pendekatan fenomenologis dan wawancara mendalam di sebuah desa di Jawa. Hasilnya menunjukkan pandangan yang bervariasi; sebagian orang tua mengapresiasi seni karena perannya dalam pembentukan karakter dan budaya, sementara sebagian meragukan prospek ekonomi di bidang ini. Seniman dianggap kreatif, namun kurang dihargai dibandingkan profesi lain yang lebih mapan. Guru seni juga sering dianggap sebagai pengajar pelengkap yang kurang penting. Temuan ini menegaskan pentingnya peran pendidikan, keluarga, dan komunitas dalam membangun dukungan terhadap profesi seni sebagai karier yang bernilai dan setara dengan profesi lain.